Influence of contrast administration side and communication with patient on motion artefact size on breast MRI - Damir Štimac; Matea Bogović; Ana Božanić; Petra Valković Zujić (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2023)
Magnetic resonance imaging is recognized as a useful modality in breast imaging. Motion is considered the most relevant cause of artefacts in breast MRI leading to degraded image quality or rendering studies non-diagnostic. The important reason for patient motion is contrast administration. Contrast administration may lead to discomfort, feeling of tingling and warmth, and pain in the arm contrast was administered to. The aim of our study was to determine the influence of contrast agent injection side and improve communication with patients on motion artifacts on subtraction reconstructions in order to prove that unexpected events may cause non-physiological movement resulting in motion artifacts, and that well-timed warning may decrease such artifacts. 146 patients with breast MRI from July 2019 to May 2020 were included. 71 of them were warned before the dynamic sequence started, and 75 of them didn't receive any warning for contrast application. The pectoral shift, in millimeters in the anteroposterior and lateral-lateral directions, was measured. Pectoral shift showed to be larger in unwarned patients when compared to warned ones with high significance (p=0.001) -no artifacts were observed in 361 warned, and 267 in unwarned women. Furthermore, artifacts were significantly larger on the side contralateral to contrast administration (median value of 2mm for the same side, and 1mm on the opposite side). In conclusion, our study showed that if patients knew the exact time of contrast application, the motion artifacts would be less pronounced; and that we should apply the contrast agent on the side opposite to the breast pathology is expected in.